PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS KEARIFAN LOKAL PADA MATERI SUHU DAN KALOR KELAS V - Endang Wardi Ningsih; Arief Kuswidyanarko; Patricia H. M Lubis (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
The fifth-grade students of SDN 1 Puding Besar have difficulty in understanding the material and heat because the presented material is not appropriated to the students’ character. It makes their learning outcomes to be unfinished. In addition, the students are not aware of the various local wisdom around them. The purpose of the study in this article was designed to develop local wisdom-based students worksheets on the valid, practical, and effective temperature and heat materials for class V. The method used was a Research and Development (R&D) research by using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The results of the study were a score for an average material expert of 96,65% with the criteria of very valid. The average score for media experts was 91,3% with the very valid criteria. The results of practicality by the classroom teacher were a score of 80% with the practical criteria. Whilst the product of practicality based on three students, small group, and large group was an average score of 92,84% with the criteria of very practical. The results of the effectiveness test product for class V was a score of 70,27% with the criteria of good. Thus, the local wisdom-based student worksheets on temperature and heat material for class V were valid, practical, and effective to use in the students’ learning process of class V at SDN 1 Puding Besar.